2001
DOI: 10.1095/biolreprod64.1.310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Testosterone on Production of Perivitelline Membrane Glycoprotein ZPC by Granulosa Cells of Japanese Quail (Coturnix japonica)1

Abstract: Avian perivitelline membrane, an investment homologous to the zona pellucida of mammalian oocytes, is composed of at least two glycoproteins. Previous studies have indicated that one of the components, a glycoprotein homologous to mammalian ZPC, is produced and secreted by the granulosa cells of developing follicles of the chicken ovary. In the present study, we evaluated the expression and regulation of ZPC in Japanese quail (Coturnix japonica) granulosa cells both in vivo and in vitro. Western blot analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 50 publications
3
40
2
Order By: Relevance
“…As reported previously in our studies, quail granulosa cells produce ZP3, which is one of the components of the PL (Pan et al 2001), whereas another constituent, ZP1, is synthesized in the liver (Sasanami et al 2003b). In the present study, we found that another minor constituent, ZPD, was produced and secreted from the granulosa cells in Japanese quail.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As reported previously in our studies, quail granulosa cells produce ZP3, which is one of the components of the PL (Pan et al 2001), whereas another constituent, ZP1, is synthesized in the liver (Sasanami et al 2003b). In the present study, we found that another minor constituent, ZPD, was produced and secreted from the granulosa cells in Japanese quail.…”
Section: Discussionsupporting
confidence: 87%
“…In avian species, at least two glycoproteins have been identified as the component of PL, ZP1, and ZP3 in quail (Pan et al 2001, Sasanami et al 2003b) and in chickens (Waclawek et al 1998, Takeuchi et al 1999, Bausek et al 2000. In addition, a recent study has revealed that a new member of the ZP protein family, ZPD, is a structural component in chicken PL (Okumura et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In avian species, three glycoproteins have been identified as the component of PL, ZP1, ZP3, and ZPD in both quail (Pan et al 2001, Sasanami et al 2003b, Sato et al 2009) and chickens (Waclawek et al 1998, Takeuchi et al 1999, Bausek et al 2000, Okumura et al 2004. These glycoproteins coordinately assemble into the fibrous matrix on the surface of the oocyte , and one of its major components, ZP1, has the ability to induce the sperm acrosome reaction in Japanese quail (Sasanami et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In birds, fertilization occurs within the infundibulum portion of the oviduct, and only the PL encloses the oocyte at the time of fertilization. At least two glycoproteins have been identified as constituents of the avian PL; ZP1 (ZPB1) and ZP3 (ZPC) in Japanese quail (Pan et al 2001, Sasanami et al 2003 and ZP1 (ZPB1), ZPB (ZPB2), ZP2 (ZPA), ZP3 (ZPC), and ZPD in chicken (Waclawek et al 1998, Bausek et al 2000, Okumura et al 2004, Smith et al 2005. We have previously cloned the cDNA encoding ZP3 (GenBank Accession no.…”
Section: Introductionmentioning
confidence: 99%